Market structure and market performance in e-commerce - Franz Hackl; Michael E. Kummer; Rudolf Winter-Ebmer; Christine Zulehner (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
We investigate the effect of market structure on market performance in the market for consumer electronics. This research is novel, because we exploit product life cycle information to build an instrumental variable for the number of firms in a market, a variable which hitherto had to be treated as exogenous in comparable studies on seller-behavior in e-commerce. We combine data from Austria's largest online site for price comparisons with retail-data on whole sale prices provided by a major hardware producer for consumer electronics. We observe input prices of firms, and all their moves in the entry and the pricing game. Using this information for 80 digital cameras, we generate instrumental variables based on the shops' entry decisions in the past. We find that instrumenting is particularly important for estimating the effect of competition on the markup of the price-leader.
Keywords: L11; L13; L81; D43; 330; Retailing; Product Life Cycle; Market Structure; Market Performance; Markup; Price Dispersion; Unterhaltungselektronik; Marktstruktur; Produktlebenszyklus; Fotohandel; Online-Handel; Mark-up Pricing; Preisdifferenzierung; Österreich